Buku Cerita Rakyat Riau Ketobong Keramat Berbasis Markerless Augmented Reality (AR) dengan Teknik User Defined Target - Michael Michael; Anggy Trisnadoli; Rahmat Suhatman (Politeknik Negeri Batam, 2019)
Folklore is a story that has been passed down from generation to generation, where each region has its own folklore. In Pelalawan District, there’s a folklore called Ketobong Keramat, where the folklore telling a story about a Magical Doctor who was willing to sacrifice his personal interests to help the King of Pelalawan. According to Malay Culture Study and Development Center, folklore is a cultural property that is not given enough attention. This can be seen in many folklore from certain regions which are quite popular but not yet known by the people in other regions. Therefore, in this final project, the Ketobong Keramat Augmented Reality application was made to the folklore. The method used in this application is the Markerless Augmented Reality Method using the User Defined Target technique, so that the Augmented Reality object can be displayed on the surface chosen by the user. Through the development of the Ketobong Keramat Augmented Reality application, it is hoped that it can increase community interest in undertaking excavations and disseminating folklore in the archipelago, as well as implementing technology on other folklore that is not yet widely known by the people of Indonesia.